Psoriasis, mental disorders and stress - Biljan, Darko (Array, 2009)
Abstract: Etiology of psoriasis is still not known and comprises a range of assumptions and very complex etiological and pathogenetic mechanisms. Along with genetical predisposition, mental disorders and stresses might have a key role in the occurrence of this disease. Total number of 70 patients suffering from psoriasis were included in the investigation. Generally accepted structured clinical interview (SCID – The Structured Clinical Interview for DSM-IV) was applied in diagnostics of mental disorders. Various mental disorders were found in as many as 90% of patients suffering from psoriasis. The most frequent mental disorders were depressive disorder (19.2%), the posttraumatic stress disorder (17.8%), alcoholism (16.4%), adaptation disorder (15.1%), anxiety – depressive disorders (13.7%) and generalized anxious disorder (9.6%). The authors have concluded that in patients with psoriasis both various mental disorders and various stress events are frequent. The results have implied that there is a link between psoriasis on the one hand and various mental disorders and various stressors on the other. The investigation implies that there is a need to improve multidisciplinary approach in diagnostics and treatment of psoriasis and multi disciplinary team should consist of dermatologist, psychiatrist and psychologist